Effectiveness of educational interventions to promote safe handling of pesticides: protocol for a systematic review and meta-analysis - Anne Cockcroft; Neil Andersson; Sergio Paredes-Solís; José Legorreta-Soberanis; Belén Madeline Sánchez-Gervacio; Víctor Manuel Alvarado-Castro; Miguel Flores-Moreno; Claudia Erika Rios-Rivera; Janet Saldaña-Almazán (BMJ Open)
Introduction Appropriate use of pesticides minimises harm to human health and the environment. Despite regulations and restrictions on use, however, many farmers still use highly toxic pesticides in ways that endanger their health and the environment. Many pesticide users know little about the health effects of these chemicals or how to handle them safely. A systematic review will collate evidence of the effectiveness of educational interventions among farmers regarding health hazards and the safe handling of pesticides. The review aims to summarise the impact of educational interventions on knowledge and reported behaviour of pesticide users and to identify characteristics of more effective interventions.Methods and analysis We will search MEDLINE, LILACS, AGRICOLA, IMBIOMED, SciELO, Web of Science, Scopus, Embase databases and from the grey literature, Open Grey and WHO to identify potentially eligible studies. We will consider randomised and non-randomised controlled trials that evaluated the impact of educational interventions among farmers about the safe use of pesticides. We will include studies published between 2000 and 2024 in English, Spanish and Portuguese and consider outcomes of knowledge about pesticide health effects, knowledge about safe handling of pesticides and reported behaviour when handling pesticides. A meta-analysis of eligible studies, using a random-effects model, will estimate the impact of educational interventions on the outcomes as the difference between the intervention group and the control group at the last point of measurement. We will assess heterogeneity using the χ2 test and I2 statistic, conduct a sensitivity analysis by removing each study from the meta-analysis and evaluate publication bias with a funnel plot and Begg and Egger tests. Subgroup analyses will examine the impact of different kinds of educational interventions.Ethics and dissemination Ethics approval is not required as no information from individuals are collected. The results will be published in a peer-reviewed journal or disseminated at relevant conferences.PROSPERO registration number CRD42023413028.